Sistema baseado em Internet das Coisas para o rastreio aplicado à logística da cadeia de frio - Garcia, Alex Fabiano (Universidade Federal de São Carlos, 2024)
This study describes the design, implementation, and validation of the System Based on the Internet of Things for Tracking Cold Chain Logistics (SBIdC-RALCF). The system aims to solve logistics challenges in remote areas by using IoT technologies to monitor and manage the conditions of perishable goods during transportation, ensuring their quality and safety. The proposed solution encompasses various sensor types and integrates multiple Long Range Wide Area Network (LoRaWAN) providers to improve coverage. It aims to support decision-makers in public-private partnerships that leverage existing infrastructure and invest in cost-effective networks to address social issues in outlying regions. The study shows how antenna coverage simulation tools provide good accuracy compared to the effective distance of the gateways that receive the Long Range (LoRa) signal. Field tests in the Netherlands demonstrate the system's effectiveness in real-world scenarios, showing features such as GPS-free geolocation by multilateration, long-range communication, and the potential for applying our solution in other domains beyond cold chain logistics.
An Internet of Things-based system for tracking applied to cold chain logistics
Keywords: Internet das coisas; Internet of things; Transporte; LoRaWAN; Transport; Independência de GPS; GPS-free; Multilateração; Multilateration; Cadeia de frio; Cold chain; Produtos perecíveis; Perishable goods; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO